Microflora of the elecampane (Inula vulgaris Ds.) from seat of growth - Косоголова, Л. О.; Небесна, Ю. М.; Веселовська, Т. Є.; Чоповська, А. О. (Problems of Environmental Biotechnology, 2018)
It was considered the data about elecampane (Inula vulgaris DS.), which have antimicrobial activity. It was determined which groups of substances are caused its specific action. The antimicrobial properties of elecampane (Inula vulgaris DS.) extraction from different places of growth were investigated.